A thermal neutron detector array communication protocol - Huang, Qi-Chang; Chen, Qi; Dong, Chunhui (Journal of instrumentation, 2022)
To assess hadronic and electromagnetic components from extensive air shower events (EAS), 16 6 Li-based ZnS (Ag) scintillator detectors combine into a thermal neutron detector array. After a shower event, each scintillator screen can concurrently catch neutrons and electrons, producing a succession of electrical signals with different pulse shapes. These signals are sampled by 16 oscilloscope-like circuits and sent over a single serial link, where EAS-related sampling results may fill each channel's memory. However, there are presently no specific studies to address data congestion in such random signal digitizers. Here, we demonstrate that decreasing the sampling rate on the trailing edge can compress data size while preserving pulse shapes and that optimizing the read/write time of memories can enhance transmission speed between asynchronous clock domains. According to test results, the 100 MHz serial transceiver can send 1996 pulses per second when only receiving data from one channel at 50 MHz rates, and it can send 242 pulses per second when simultaneously receiving data from 32 channels (16 × 2). This method increases transmitting speeds 2.3 times over previously employed algorithms, and the compressed rate reaches 97.74%. In addition, we found that the total error rate is lower than 10–10. Our findings also show how memory controllers would probably operate in data flows of 32 channels, predicting the slower writing time and the faster reading time that can complete sending a packet of one channel in the shortest time. We anticipate that our assay can help more detector arrays that require waveform transmission.